Components of Metabolic Syndrome in Korean Adults: A Hospital-Based Cohort at Seoul National University Bundang Hospital - Lim, Soo (J Obes Metab Syndr, 2019)
BACKGROUND: The prevalence of metabolic syndrome is increasing in Korea, particularly among young adults. This trend will increase the incidence of cardiovascular and metabolic diseases in the future. Therefore, it is imperative to detect and prevent metabolic abnormalities early in life. Here, we established a hospital-based biobank cohort to identify the most prevalent dysmetabolic phenotype. The aim of this report was to inform other researchers of our protocol and to share our data for future collaboration. METHODS: The baseline examination comprised health-related questionnaires, anthropometric and handgrip strength measurements, bioelectrical impedance analysis of body composition, and nutritional assessment. Relevant biochemical parameters were measured, and oral glucose tolerance tests were performed. Metabolic syndrome was defined according to the National Cholesterol Education Program Adult Treatment Panel III criteria with Asian waist circumference criteria. RESULTS: From a total of about 3,000 employees aged 20 to 59 years working at Seoul National University Bundang Hospital, 1,017 were enrolled from 2015 to 2016. The mean age was 34.5±8.4 years for men (n=311, 30.6%) and 30.9±8.5 years for women (n=706, 69.4%). The overall prevalence of metabolic syndrome was 7.6% (17.7% in men and 3.1% in women). Among the five components of metabolic syndrome, high blood pressure was the most prevalent in both men (51.4%) and women (13.8%). CONCLUSION: Although further follow-up data are needed, we expect that more adverse cardiovascular events may occur in men than in women. This hospital-based cohort will serve as the foundation for a comprehensive evaluation of metabolic syndrome and future cardiometabolic disease risk in middle-aged Koreans.